2021
DOI: 10.1002/jor.24997
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of distinct perivascular cell subsets for intra‐articular cell therapy in posttraumatic osteoarthritis

Abstract: Intra-articular injection of mesenchymal stem cells has shown benefit for the treatment of osteoarthritis (OA). However, mesenchymal stem/stromal cells at the origin of these clinical results are heterogenous cell populations with limited cellular characterization. Here, two transgenic reporter mice were used to examine the differential effects of two precisely defined perivascular cell populations (Pdgfrα + and Pdgfrβ + cells) from white adipose tissue for alleviation of OA. Perivascular mesenchymal cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Seventeen studies evaluated the effects by imaging analysis: nine studies (52.9%) reported significant differences in favour of adipose-derived products, while eight studies observed no differences. In particular, micro-computed tomography (micro-CT) evaluation was performed in six studies, with positive effects in five studies in terms of prevention of cartilage and subchondral bone degeneration and improvement of bone thickness and volume [23][24][25][26][27]. Radiographic evaluation was performed in 6 studies with only one study showing a statistically significant difference in favour of adipose-derived products [28].…”
Section: Imaging Analysismentioning
confidence: 99%
“…Seventeen studies evaluated the effects by imaging analysis: nine studies (52.9%) reported significant differences in favour of adipose-derived products, while eight studies observed no differences. In particular, micro-computed tomography (micro-CT) evaluation was performed in six studies, with positive effects in five studies in terms of prevention of cartilage and subchondral bone degeneration and improvement of bone thickness and volume [23][24][25][26][27]. Radiographic evaluation was performed in 6 studies with only one study showing a statistically significant difference in favour of adipose-derived products [28].…”
Section: Imaging Analysismentioning
confidence: 99%
“…OARSI grading ranged from G1 to G6. OARSI score was calculated according to the formula: score = grade (G1 to G6) × stage (S1 to S4) 20,21 . OARSI score ranged from 0-24. was determined according to the formula: score = grade (G1 to G6) × stage (S1 to S4) 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…OARSI grading ranged from G1 to G6. OARSI score was calculated according to the formula: score□=□grade (G1 to G6)□×□stage (S1 to S4) 20,21 . OARSI score ranged from 0–24.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the bone loss and fracture risk associated with cancer therapy; in bone marrow transplantations, metastatic bone disease, and cancer settings, the re-establishment of bone marrow microenvironments after chemotherapy and radiation is crucial for the effective treatment outcome and clinical management of these conditions (Chen et al, 2012; D’Oronzo et al, 2019; Singh et al, 2019; Tsukamoto et al, 2021; Vi et al, 2018; Wu et al, 2018). The bone vasculature and perivascular mesenchymal stem cells, which can differentiate to generate bone cells, adipocytes and chondrocytes, are essential for bone growth, and hematopoietic stem cell (HSC) maintenance (Hsu et al, 2021; James & Péault, 2019; Kusumbe et al, 2016). The manipulation of the vasculature is sufficient for the improvement of vascular HSC niche function, which suggests the existence of molecular pathways coupling the behaviour of endothelial cells and perivascular mesenchymal stem progenitor cells (MSPCs) in bone (Hanoun et al, 2014; Ramasamy, 2017).…”
Section: Introductionmentioning
confidence: 99%